Numerical study of flow field on molten iron desulfurization with mechanical stirring. (July 2016) - Xiao, Linwei; Chen, Kuisheng; Dan, Binbin; Rong, Zhijun; Wang, Rui
The flow field of molten iron in the desulfurization process utilizing the mechanical stirring method under three different conditions was investigated using numerical simulation. The three conditions were central and eccentric stirring with the standard impeller and central stirring with the worn impeller, respectively. Three 1/20-scale numerical models were established and four inspection regions were set up on them. In all, 600 sets of instantaneous velocity fields for each model were exported and proper orthogonal decomposition technique was applied to deal with the data. The macroscopic flow field in the normal model operating under standard conditions was analyzed, which found that the mean flow has a relatively large fluctuation in flow field despite having a high proportion in total kinetic energy. A steady close relationship was revealed between the first two modes by studying the correlation of their coefficients. The first four modes were comparatively analyzed, which reflected that the change in the mean flow in the ladle using a worn impeller is slow and eccentric stirring is beneficial to desulfurization due to the asymmetry of the flow field on two sides.